2018
DOI: 10.3390/rs10060919
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Agung (Indonesia) Ash Plume of November 2017 by Means of Infrared Himawari 8 Data

Abstract: Abstract:The Agung volcano (Bali; Indonesia) erupted in later November 2017 after several years of quiescence. Because of ash emissions, hundreds of flights were cancelled, causing an important air traffic disruption in Indonesia. We investigate those ash emissions from space by applying the RST ASH algorithm for the first time to Himawari-8 data and using an ad hoc implementation scheme to reduce the time of the elaboration processes. Himawari-8 is a new generation Japanese geostationary meteorological satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…One could also argue that the large model spread, as described by Marshall et al (2018) and Zanchettin et al (2016), limits the interpretation of our model results. Other models may obtain quantitatively different results, but most probably the simulated difference between the two eruption scenarios would be qualitatively similar: a lower radiative forcing of the Agung 1963 eruption when including two eruption phases.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One could also argue that the large model spread, as described by Marshall et al (2018) and Zanchettin et al (2016), limits the interpretation of our model results. Other models may obtain quantitatively different results, but most probably the simulated difference between the two eruption scenarios would be qualitatively similar: a lower radiative forcing of the Agung 1963 eruption when including two eruption phases.…”
Section: Discussionmentioning
confidence: 87%
“…Earthquakes, steam, ash clouds, and lahars resulted in the evacuation of nearly 150 000 people from the volcano's environment within a radius of 9-12 km in November 2017 (Gertisser et al, 2018). The eruption resulted in an ash cloud reaching up to an altitude of about 9.3 km (Marchese et al, 2018) and about 10 DU SO 2 above Bali (Hansen, 2017), which was not large and high enough to result in a climatic impact. The last climatic eruption of Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a group of colorized 3D images of soybean plants were divided into fifteen single areas for 15 pots automatically according to spatial information. Finally, the reconstructed 3D plant points were used to calculate the following three phenotypic traits for each soybean plant: (1) the plant height (H) was the shortest distance from the upper boundary of the main photosynthetic tissues (excluding inflorescences) of a plant to the ground level [40]; (2) the canopy breadth, which consisted of two aspects: the width across-row (WAR) distance is the distance along the x-axis, while the width in-row (WIR) distance is the distance along the y-axis [30]; and (3) the color indices in the HSI color space.…”
Section: Overall Process Flow For Calculating Phenotypic Traitsmentioning
confidence: 99%
“…The above studies confirmed the abilities of color indices to assess plant health.Increasing the throughput of phenotyping is a great challenge in plant genetics, physiology, and breeding [27]. To improve the accuracy and efficiency of phenotyping methods, different types of sensor techniques, such as the use of RGB (Red-Green-Blue) cameras, ToF (Time of Flight) cameras, and 3D laser-scanning devices [28][29][30], have been introduced.…”
mentioning
confidence: 99%
“…Earthquakes, steam, ash clouds and lahars resulted in the evacuation of nearly 150.000 people from the volcano's environment within a radius of 9-12 km in November 2017 (Gertisser et al, 2018). Finally, the eruption resulted in an ash cloud reaching up to an altitude of about 9.3 km (Marchese et al, 2018) and about 10 DU SO 2 above Bali (Hansen, 2017), which was not large and high enough to result 20 in a climatic impact. The last climatic eruption of Mt.…”
Section: Introductionmentioning
confidence: 99%